Restless Watchdog: Selective Quickest Spectrum Sensing in Multichannel Cognitive Radio Systems. (1st September 2009) - Li Li, Husheng Husheng
Abstract : Selective quickest spectrum sensing, which monitors the spectrum activity in multiple channels, is studied for multichannel cognitive radio systems with nonnegligible channel switching time (blind period). The spectrum sensor needs to detect the emergence of primary users as quickly as possible. Due to hardware limitation, it is assumed that only a subset of frequency channels can be monitored simultaneously. The problem of controlling the monitoring procedure is studied in the frameworks of dynamic programming (DP). System states and cost functions are defined. Cost-to-go functions for DP are derived, simplified, and approximated, based on which control policies are derived. Numerical results are provided to demonstrate the proposed algorithms.